2015
DOI: 10.1016/j.jgr.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng inhibits apoptosis in neuroblastoma cells via estrogen receptor β-mediated phosphatidylinositol-3 kinase/Akt signaling

Abstract: BackgroundGinseng has been shown to exert antistress effects both in vitro and in vivo. However, the effects of ginseng on stress in brain cells are not well understood. This study investigated how Korean Red Ginseng (KRG) controls hydrogen peroxide-induced apoptosis via regulation of phosphatidylinositol-3 kinase (PI3K)/Akt and estrogen receptor (ER)-β signaling.MethodsHuman neuroblastoma SK-N-SH cells were pretreated with KRG and subsequently exposed to H2O2. The ability of KRG to inhibit oxidative stress-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Cell cytotoxicity was measured by quantitative colorimetric assay with a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenylterazolium bromide (MTT) assay as described elsewhere (Nguyen et al, 2015). Breast cancer cells were seeded at a concentration of 1 × 10 5 cells/well in 96-well plates and treated with Saxi A for 24 h. The cells were washed once with D-PBS and incubated with 25 mg/ml of MTT (Sigma, St. Louis, MO) for 4 h at 37°C and 5% CO 2 .…”
Section: Mtt Assaymentioning
confidence: 99%
“…Cell cytotoxicity was measured by quantitative colorimetric assay with a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenylterazolium bromide (MTT) assay as described elsewhere (Nguyen et al, 2015). Breast cancer cells were seeded at a concentration of 1 × 10 5 cells/well in 96-well plates and treated with Saxi A for 24 h. The cells were washed once with D-PBS and incubated with 25 mg/ml of MTT (Sigma, St. Louis, MO) for 4 h at 37°C and 5% CO 2 .…”
Section: Mtt Assaymentioning
confidence: 99%
“…Ginsenoside Rg2 reduced glutamate-induced cell death significantly through mechanisms related to anti-apoptosis and anti-oxidation in PC12 cells (Li et al 2007). A few studies also reported that the water extract of KRG protected cultured cortical cells from amyloid-β-induced apoptosis (Kim et al 2014) and repressed apoptosis in SK-N-SH cells by suppressing oxidative stress (Nguyen et al 2015). Therefore, the ginsenosides may play an important role in the observed prevention of apoptotic cell death in response to the KRG extract, but the possibility that other substances are involved in the anti-apoptotic effect still remains.…”
Section: Discussionmentioning
confidence: 99%
“…While the intrinsic pathway activates with the release of cytochrome-c from the mitochondria, the extrinsic pathway activates by ligand binding to death receptors such as Fas and tumor necrosis factor receptor-1 (TNFR1) [3-7, 9, 10] . Some candidate agents such as sodium thiosulfate, D-or L-methionine, lipoic acid, N-acetyl cysteine, acetyl L-carnitine, alpha tocopherol, and resveratrol were studied both in vitro and in vivo to analyze their protective effects against CDDP-induced ototoxicity [7,16,[18][19][20][21] . However, none of them are currently approved for usage against CDDP-induced ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that KRG mainly works by inhibition of some proapoptotic genes such as caspase-1, caspase-3, and the TNF family of genes and by enhancement of antiapoptotic gene expression such as bcl-2 [8][9][10][11][12][13] . On the other hand, KRG has antiapoptotic effects on neuronal tissues [18] . It was shown that this effect mainly works by up regulation of the p13K/Akt signaling pathway, which is a cell survival pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation